Dampak Pembiayaan Mikro Syariah terhadap Kesejahteraan Pelaku UMKM - Sitti Harnita Rumasukun; Nani Hanifah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This article discusses the impact of Islamic microfinance on the welfare of micro, small, and medium enterprises (MSMEs) in Indonesia. The research aims to examine how sharia-based financing schemes contribute to the development and sustainability of MSMEs. This qualitative-descriptive study used literature review and documentation methods. Findings indicate that Islamic microfinance through contracts such as murabahah and mudharabah significantly enhances business productivity and financial independence of MSME actors. It also strengthens ethical business behavior and local economic growth. However, implementation challenges remain, particularly in terms of financial literacy and institutional outreach. The study recommends broader digital-based Islamic financial inclusion to reach underserved communities. These results are relevant for stakeholders interested in sustainable economic empowerment through sharia finance.